Radical Recreation: Non-Iconic Movements of Tradition in Keralite Classical Dance - Lemos, Justine (Recherches sémiotiques / Semiotic Inquiry, 2012)
Many studies assume that dance develops as a bearer of tradition through iconic continuity (Downey 2005; Hahn 2007; Meduri 1996, 2004; Srinivasan 2007, 2011, Zarrilli 2000). In some such studies, lapses in Iconic continuity are highlighted to demonstrate how “tradition” is “constructed”, lacking substantive historical character or continuity (Meduri 1996; Srinivasan 2007, 2012). In the case of Mohiniyattam – a classical dance of Kerala, India – understanding the form’s tradition as built on Iconic transfers of semiotic content does not account for the overarching trajectory of the forms’ history. Iconic replication of the form as it passed from teacher to student was largely absent in its recreation in the early 20th century. Simply, there were very few dancers available to teach the older practice to new dancers in the 1960s. And yet, Mohiniyattam dance is certainly considered to be a “traditional” style to its practitioners. Throughout this paper I argue that the use of Peircean categories to understand the semiotic processes of Mohiniyattam’s reinvention in the 20th century allows us to reconsider tradition as a matter of Iconic continuity. In particular, an examination of transfers of repertoire in the early 20th century demonstrates that the “traditional” and “authentic” character of this dance style resides in semeiotic processes beyond Iconic reiteration; specifically, the “traditional” character of Mohiniyattam is Indexical and Symbolic in nature.